Living Hadith in the Tekuinan Tradition: Study at the Al Munawar Mosque, Kejambon Village, Tegal City - Rahmahani Nur Safitri; Nurul Maisyal (AQWAL Journal of Qur'an and Hadis Studies, 2022)
Maulid Nabi is one of the most developed traditions in Indonesian society. Almost all regions have their own characteristics in the tradition of celebrating the Prophet's Maulid. The celebration of the Prophet's Maulid in various regions is held every 12 Rabiul Awwal as gratitude for the birth of the Prophet. However, there is something unique about one of the traditions in Tegal, namely the Tekuinan Tradition. This tradition aims to welcome the birthday of the Prophet, but its implementation is not on the 12th but on the 8th of Rabiul Awwal. In fact, this tradition also has its own meaning for the local community and scholars. Through a phenomenological approach, this paper discusses the Tekuinan tradition at the Al-Munawar mosque, Kejambon Village, Tegal City. The results of which state that it is a Living Hadith because basically this tradition is inspired by a poem in the Barzanji book, which is mostly sourced from hadith. In this paper, we will discuss the understanding of the community and scholars towards this tradition and also what traditions are brought to life in the Tekuinan tradition.